Collapse Assessment for Code-Conforming Reinforced Concrete Frame Structures in Romania - Pavel, Florin (Frontiers in Built Environment, 2018)
In this study, two RC frame structures having five stories and nine stories, respectively are designed using the current Romanian seismic code. The seismic performance is evaluated by integrating the site-specific seismic hazard with the structural fragility. The results show, as expected, a large scatter in the values of the collapse annual rates. The smallest annual collapse rates correspond to sites under the influence of shallow crustal seismic sources, while the largest ones are observed in sites under the influence of the Vrancea intermediate-depth seismic source. In addition, based on the results obtained, a larger seismic risk can be associated to the five-story structure. The study also shows that it is vital to develop a seismic hazard model that captures the long-period spectral amplifications observed at sites in southern Romania.